Metode Pemberian Makan dan Kejadian Tengkes Studi di Kecamatan Labuhan Haji Kabupaten Lombok Timur - Robyan E. Bafadal (Universitas 45 Surabaya, 2024)
One of the health problems faced by East Lombok Regency concerns tengkes babies. From year to year the number of tengkes babies is decreasing but is still above the national figure, let alone the ideal figure. This research tries to link the method of feeding with the incidence of tengkes babies. Through in-depth interviews and observations, it was discovered that the main cause of tengkes babies was responsive feeding. This means that many babies receive portions of food that do not match their needs.